Life of the Antarctic ice : from deep inland to the coast - Matsuoka, Kenichi (ed.) (Norwegian Polar Institute, 2020)
Keywords: Antarktis; Dronning Maud Land; glasiologi; innlandsis; isbreer; klimaendringer; polarforskning; snø

Revisiting perceptions and evolving culture: a community dialogue on women in polar research - Starkweather, Sandra; Seag, M; Lee, O; Pope, A (Polar Research, 2018)
Women have made outstanding contributions to polar research in recent decades, though full engagement may be hindered by persistent inequities, including notably the prevalence of workplace harassment. Remote field settings, such as those pervasive in polar research, have been identified as particularly susceptible to cultures of harassment. It was therefore timely at the Polar 2018 Open Science Conference in Davos, Switzerland, to convene a discussion focused on women’s perspectives and experiences. A panel discussion—“From Entering the Field to Taking the Helm: Perspectives of Women in Polar Research”—took place on 20 June 2018 and featured five women undertaking work from marine biotechnology to organizational leadership, across career levels. Over 300 conference attendees joined the lunchtime panel. The panellists’ perspectives on historical barriers, current challenges and future prospects revealed that while challenges persist, experiences vary greatly. Audience engagement underscored the need to sustain dialogue at polar meetings, to bring visibility to the statistics related to workplace harassment and to encourage polar science organizations to assume leadership on promoting equitable workplace culture.
Keywords: Antarktis; arbeidsmiljø; kjønn; kultur; likestilling; polarforskning; sosiologi; trakassering; vitenskap

C.A. Larsen : explorer, whaler & family man - Riffenburgh, Beau (Red.); Kløver, Geir O (Red.) (The Fram Museum, 2016)
Keywords: Antarctic ekspedisjonen; Antarktis; Carl Anton Larsen; D/S Antarctic; D/S Jason; Jason ekspedisjonene; Weddellhavet; hvalfangere; hvalfangst; oppdagelsesreiser; polarforskning

Norway in the Antarctic - Rognhaug, Magnus Hovind (ed.) (Norsk Polarinstitutt, Norge Utenriksdepartementet, 2014)
Keywords: Antarktis; Antarktistraktaten; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Norge i Antarktis - Rognhaug, Magnus Hovind (red.) (Norsk Polarinstitutt, 2014)
Keywords: Antarktis; Antarktistraktaten; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Sørishavet; forskning; miljøvern; polarforskning; politikk

The state of the poles : climate lessons from the International Polar Year - Bjørnæs, Christian; Prestrud, Pål (Unipub, 2012)
Keywords: Antarktis; klimaendringer; polarforskning; polarområdene

Norges ti viktigste polarekspedisjoner - Jaklin, Asbjørn; Jølle, Harald Dag (Norsk Polarinstitutt, 2012)
Keywords: Antarktis; Carl Anton Larsen; Maudheim; NSBX 1949-52; Norge; Norsk-britisk-svenske antarktisekspedisjon; Roald Amundsen; Sydpolsekspedisjonen; polarekspedisjoner; polarforskning; polarområdene

Polar settlements : location, techniques and conservation - Barr, Susan (red.); Chaplin, Paul (red.) (ICOMOS International Polar Heritage Committee, 2011)
Keywords: Antarktis; hvalfangststasjoner; kulturminnevern; polarforskning; polarområdene; turisme

Krill og økosystemtokt med G.O.Sars i Sørishavet - Iversen, Svein A (Polaråret 2007-2008 : det norske bidraget, 2011)
Keywords: Bouvetøya; Det Internasjonale polaråret 2007; krill; marine økosystemer; plankton; polarforskning

Ecosystem study and krill survey aboard G.O. Sars in Southern Ocean - Iversen, Svein A; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Bouvetøya; Det Internasjonale polaråret 2007; krill; marine økosystemer; plankton; polarforskning

Seler brukt som "forskningsassistenter" for å utforske polhavene - Kovacs, Kit M (Polaråret 2007-2008 : det norske bidraget, 2011)
Keywords: Det Internasjonale polaråret 2007; Sørishavet; polarforskning; polarområdene; seler; sjøpattedyr

Seals used as "research assistants" in the polar oceans - Kovacs, Kit M; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Det Internasjonale polaråret 2007; Sørishavet; polarforskning; polarområdene; seler; sjøpattedyr

Clues to historical climate variation and future changes in sea level buried in the Antarctic ice (TASTE-IDEA) - Winther, Jan-Gunnar; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Det Internasjonale polaråret 2007; Dronning Maud Land; glasiologi; havnivåstigning; klimaendringer; polarforskning

Svarene på fortidens klimavariasjoner og framtidens havnivå ligger begravd i isen i Antarktis - Winther, Jan-Gunnar; Isaksson, Elisabeth (Polaråret 2007-2008 : det norske bidraget, 2011)
Keywords: Det Internasjonale polaråret 2007; Dronning Maud Land; glasiologi; havnivåstigning; klimaendringer; polarforskning

Vår glemte polarhelt : Carsten Borchgrevink og Southern Cross-ekspedisjonen 1898-1900 - Vogt, David (Aschehoug, 2008)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Nordmenn; Ole Must; Per Savio; Southern Cross; Sydpolen; biografier; ekspedisjonen; ekspedisjoner; oppdagelsesreiser; polarforskning; polarområdene; samisk

Klimagåten Antarktis - Winther, Jan-Gunnar (Gyldendal, 2008)
Keywords: Antarktis; IPY; Sydpolen; ekspedisjoner; internasjonale polarår; isbreer; klimaendringer; klimatologi; polarforskning

Norge i Antarktis : fra erobring til moderne forskning - Winther, Jan-Gunnar; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Tveraa, Torkild; Monsen, Oddbjørn (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Norway in the Antarctic : from conquest to modern science - Winther, Jan-Gunnar; Tveraabak, Jacob; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Monsen, Oddbjørn; Goldman, Helle V (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Pionerforskning i Sørishavet. Kappløpet mot Sydpolen - Berg, Kåre; Brenna, Åsta (Polarheltene : norske pionerer i Arktis og Antarktis, 2003)
Keywords: Antarktis; Carl Anton Larsen; Carsten Borchgrevink; Roald Amundsen; Sydpolen; biografier; oppdagelsesreiser; polarekspedisjoner; polarflyving; polarforskning; polarhelter

Pioneering exploration in the Antarctic Ocean. The race for the South Pole - Berg, Kåre; Brenna, Åsta; Aase, Jean (Heroes of the polar wastes : pioneer Norwegian explorers in the Arctic and the Antarctic, 2003)
Keywords: Antarktis; Carl Anton Larsen; Carsten Borchgrevink; Roald Amundsen; Sydpolen; biografier; oppdagelsesreiser; polarekspedisjoner; polarflyving; polarforskning; polarhelter